1990
DOI: 10.1007/bf01101711
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrogen peroxide in the in vitro cytotoxicity of 3-hydroxykynurenine

Abstract: Previous studies have indicated that the generation of H2O2 may be a key step in the mechanism mediating the in vitro cytotoxicity of 3-hydroxykynurenine (3HK). An exposure protocol resulting in a delayed toxicity was utilized in order to further examine the role of H2O2 in the in vitro toxicity of 3HK in a neural hybrid cell line. 3HK-induced cell lysis was significantly attenuated by administration of catalase after termination of 3HK exposure and was abolished when intracellular peroxidase activity was elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 26 publications
0
66
0
1
Order By: Relevance
“…According to some early studies, the proposed deleterious effects of 3-OH-L-KYN, a metabolite produced by kynurenine 3-monooxygenase (KMO), are mediated by free radicals and not glutamate receptors, and some of its detrimental actions may be due to its metabolite, 3-OH-ANA, via its auto-oxidation, leading to the production of superoxide anion [218][219][220][221].…”
Section: -Hydroxy-l-kynurenine and 3-hydroxyanthranilic Acidmentioning
confidence: 99%
“…According to some early studies, the proposed deleterious effects of 3-OH-L-KYN, a metabolite produced by kynurenine 3-monooxygenase (KMO), are mediated by free radicals and not glutamate receptors, and some of its detrimental actions may be due to its metabolite, 3-OH-ANA, via its auto-oxidation, leading to the production of superoxide anion [218][219][220][221].…”
Section: -Hydroxy-l-kynurenine and 3-hydroxyanthranilic Acidmentioning
confidence: 99%
“…The second neurotoxic Trp metabolite is 3-HAA, which is unstable under physiological conditions. Upon spontaneous auto-oxidation, 3-HAA produces reactive radical species, which in turn induce oxidative stress and apoptosis in neurons [57][58][59].…”
Section: Possible Mechanisms Of Ido-mediated Tolerance Inductionmentioning
confidence: 99%
“…All the above syndromes are characterized by severe neurological dysfunctions. Moreover, earlier studies using a neuronal hybrid cell line have shown that 3-HK exerts cytotoxicity and causes cell lysis (9,10). Nevertheless, the argument that 3-HK may be involved in brain pathogenesis has long been dismissed (11).…”
mentioning
confidence: 99%